Pemetaan Daerah Penangkapan Potensial Ikan Demersal Dengan Kapal Latih KM. Coelacanth Di Perairan Bitung Sulawesi Utara - Darondo, Franky Adrian; Manohas, Jul; Putri, Elsari Tanjung; Karyanto, Karyanto; Santoso, Heru; Katili, Lidya; Hamel, Samuel; Tauladani, Saeful A.; Simau, Silvester; Saranga, Rudi; Antou, Lusje D.; Pontoh, Peggy; Akbar, Mohammad; Purwanto, Yuli (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
The waters of Bitung, located in North Sulawesi Province, have long been known for their rich underwater biodiversity, specifically unique and exotic creatures. They are a potential demersal fishing ground for coastal fishermen in Bitung City. However, information on demersal fishing grounds is limited, so it is necessary to conduct research and map demersal fishing grounds in Bitung waters. This study aims to obtain data on the geographical position of demersal fishing areas in Bitung waters to be mapped into a map of demersal fishing areas in Bitung waters and determine the types of catches from bottom fishing rods. Data was collected directly by following demersal fishing operations on the training ship FV. Coelacanth. The data were analyzed using survey methods and direct observation, which is an effort to collect information directly from a part of the population that is considered a specified population and has the nature of authentication or checking of existing theories. The study's results obtained geographical data on demersal fishing areas in Bitung waters at (1) 10°23.447' N, 125°06.934' E (Suar Batu Kapal area),, (2) 10°23.483' N, 125°09.567' E (Karang Tanjung Merah area) (3) 10°23.283' N, 125°10.852' E (Batu Angus Area), (4) 10°30.393' N, 125°15.392' E (Menara Lampu Hijau Area), and (5) 10°32.706' N, 125°18.105' E (Dua Pulau area). The primary catches of bottom fishing consist of fish species: grouper, snapper, trevally fish, Gora fish, emperor fish and parrot fish.